Smoldering multiple myeloma risk factors for progression: a Danish population‐based cohort study. (5th February 2016) - Sørrig, Rasmus; Klausen, Tobias W.; Salomo, Morten; Vangsted, Annette J.; Østergaard, Brian; Gregersen, Henrik; Frølund, Ulf Christian; Andersen, Niels F.; Helleberg, Carsten; Andersen, Kristian T.; Pedersen, Robert S.; Pedersen, Per; et al.
Abstract: Several risk scores for disease progression in patients with smoldering multiple myeloma (SMM) have been proposed; however, all have been developed using single‐center registries. To examine risk factors for time to progression (TTP) to multiple myeloma (MM) for SMM, we analyzed a nationwide population‐based cohort of 321 patients with newly diagnosed SMM registered within the Danish Multiple Myeloma Registry between 2005 and 2014. Significant univariable risk factors for TTP were selected for multivariable Cox regression analyses. We found that both an M‐protein ≥30 g/L and immunoparesis significantly influenced TTP (HR 2.7, 95%CI (1.5;4.7), P = 0.001, and HR 3.3, 95%CI (1.4;7.8), P = 0.002, respectively). High free light chain (FLC) ratio did not significantly influence TTP in our cohort. Therefore, our data do not support recent IMWG proposal of identifying patients with FLC ratio above 100 as having ultra high‐risk of transformation to MM. Using only immunoparesis and M‐protein ≥30 g/L, we created a scoring system to identify low‐, intermediate‐, and high‐risk SMM. This first population‐based study of patients with SMM confirms that an M‐protein ≥30 g/L and immunoparesis remain important risk factors for progression to MM.